2010
DOI: 10.1177/1477370810367014
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the international decline in crime rates

Abstract: This paper examines aggregate crime trends and variation around them from 1988 to 2004 for 26 countries and five main crime types using data from the International Crime Victims Survey. Multilevel statistical analysis is used to identify the main trends. Major drops in crime were experienced in many countries from the early to mid-1990s onwards. The current analysis estimates that between 1995 and 2004, the mean international crime incidence reductions were: 77.1 percent in theft from cars, 60.3 percent in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
92
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(97 citation statements)
references
References 10 publications
3
92
0
2
Order By: Relevance
“…However, since the majority of the population does not, in fact, suffer any crime (Prieto Curiel and Bishop, 2016b) fear of crime is thus the result of a more complex social dynamics which does involve the victims of crime but also involves other social aspects. Crime is, relatively speaking, a rare event (Tseloni et al, 2010) tending to be highly concentrated so that, unfortunately, a particular person, a business, or a street may suffer a much higher number of crimes than the others (Farrell and Pease, 1993;Farrell, 2015;Pease, 1998;Brantingham and Brantingham, 2010;Johnson, 2010). But the fact that crime is rare and highly concentrated also means that fear of crime is more frequent than crime itself (Grogger and Weatherford, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, since the majority of the population does not, in fact, suffer any crime (Prieto Curiel and Bishop, 2016b) fear of crime is thus the result of a more complex social dynamics which does involve the victims of crime but also involves other social aspects. Crime is, relatively speaking, a rare event (Tseloni et al, 2010) tending to be highly concentrated so that, unfortunately, a particular person, a business, or a street may suffer a much higher number of crimes than the others (Farrell and Pease, 1993;Farrell, 2015;Pease, 1998;Brantingham and Brantingham, 2010;Johnson, 2010). But the fact that crime is rare and highly concentrated also means that fear of crime is more frequent than crime itself (Grogger and Weatherford, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The second was that most other high income countries experienced a crime decline. Hence the collection of work edited by van Dijk et al (2012) refers to an international crime drop (see also Tseloni et al 2010;Knepper 2012;Tonry 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Homicide statistics, Criminal Justice sources, latest available year, 2003-2008SOURCE: UNODC, 2011a A large group of hypotheses is found in the international literature to explain recent changes in criminality and homicide figures in several developed countries (AEBI and LINDE, 2010;BARBAGLI, 2000;BARKER, 2010;BAUMER, 2008;BLUMSTEIN and WALLMAN, 2006;FOX, 2006;HAGAN, 1994;HAGEDORN and RAUCH, 2004;HUME, 2007;KILLIAS and AEBI, 2000;MORO, 2006;PEARCE, 2006;RENNISON and PLANTY, 2006;RODGERS, 2006;WALLMAN and BLUMSTEIN, 2006;WILKINSON, 2005;ZIMRING and FAGAN, 2000). As is usual in Social Sciences, no consensus can be verified among the authors about the capacity of these hypotheses to explain factors related to the evolution of criminality and homicide/assault, an opinion shared by Tseloni et al (2010). Farrell (2013 singles out and analyzes 15 of those hypotheses related to: "…lead poisoning; abortion legalization; drug markets; demographics; policing numbers and strategies; imprisonment; strong economies; the death penalty; gun control; gun concealment; immigration; consumer confidence; the civilizing process; and improved security."…”
Section: Introductionmentioning
confidence: 99%
“…Some authors include Brazil as part of an international decline in crime rates (see TSELONI et al, 2010). Nonetheless, the subsequent years showed that this short-lived downward trend was just part of what is now perceived as oscillations around a plateau.…”
Section: Introductionmentioning
confidence: 99%